Certificate of Land Property Rights as an Evidence in Land Dispute Settlement - Marten Bunga; Robby Waluyo Amu; Leni Dwi Nurmala (CV. Rayyan Dwi Bharata, 2023)
The goal to be achieved in this writing is to study specifically about certificates of ownership as a means of evidence in resolving land disputes with problem limitations, namely: How is the strength of proof of certificates of Land Rights in land dispute resolution. The research method used is normative juridical research. Namely legal research by conducting a review of literature related to problems with a statutory approach. The results of the study show that land ownership certificates issued by the National Land Agency have strong evidentiary power to be used as evidence in resolving land disputes that are carried out either by deliberation or through the settlement process in the judiciary.